Thinking of strengthening education on nursing of infectious disease under the challenges of emerging infectious diseases (新发传染病背景下对加强传染病护理教育的思考) - NING Chuanyi (宁传艺); JIANG Li (蒋莉) (中西医结合护理)
Emerging infectious disease is one of the most improtant factors threatening individual health, influencing the stability of the society and affecting economic development. The Newely emerging infectious diseases raise a new challenge for hjelath education on nursing of infectious diseases. This paper discussed the shortcomings in infectious disease nursing teaching and provided targeted stratigies to enhance the education. (新发传染病已成为威胁人类健康、影响社会稳定和经济发展的重要因素之一。当前新发传染病不断涌现的背景给传染病护理的教学带来了新的挑战。本文针对目前传统传染病护理教学中存在的不足, 提出加强传染病护理的应对策略。)